IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) BERDASARKAN GLOBAL REPORTING INITIATIVE GUIDELINES (Studi Kasus PT Holcim Indonesia Tbk Tahun 2012-2014) - Vitria Zhuanita Rani (Jurnal Ilmiah Mahasiswa FEB, 2015)
The purpose of this study is to provide information and understanding on the implementation of reporting Corporate Social Responsibility (CSR) in the Sustainability Report. The study was conducted by comparing the CSR report disclosed the company with a standard Global Reporting Initiative (GRI) as well as understand the things the company has done in implementing CSR. The subjects were PT Holcim Indonesia Tbk by using sustainability report in 2012 until 2014. The research method used in this research is qualitative descriptive. The conclusion of this study PT Holcim Indonesia Tbk as a whole is still not fully meet the GRI standards. For 3 years, the average implementation of the CSR report in accordance with GRI only 50%, but in practice the PT Holcim Indonesia Tbk has done practices that are beneficial to the environment and society in the long term. Implementation of CSR report to GRI standard is the highest is in the environmental category.Keywords: Sustainability Report, Global Reporting Initiative, PT Holcim Indonesia Tbk, 2012-2014